Surgical Treatment of Cystic Adventitial Disease of the Popliteal Artery: Five Case Reports - Kimihiro Igari; Toshifumi Kudo; Takahiro Toyofuku; Yoshinori Inoue (Case Reports in Vascular Medicine)
Cystic adventitial disease (CAD) is a rare cause of intermittent claudication and nonatherosclerotic conditions in middle-aged men without cardiovascular risk factors. The etiology of CAD is unclear; however, the direct communication between a cyst and a joint is presumed to be a cause. We herein report a case series of CAD of the popliteal artery (CADPA), in which patients were treated with surgical resection and vascular reconstruction. Although less invasive treatment modalities, including percutaneous cyst aspiration and percutaneous transluminal angioplasty, have been the subject of recent reports, these treatments have had a higher recurrence rate. Therefore, all of the CAPDA cases in the present series were treated surgically, which lead to good outcomes.